2014
DOI: 10.1589/jpts.26.771
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasoning of Physical Therapists regarding In-hospital Walking Independence of Patients with Hemiplegia

Abstract: [Purpose] Physical therapists must often determine whether hemiparetic patients can walk independently. However, there are no criteria, so decisions are often left to individual physical therapists. The purpose of this study was to explore how physical therapists determine whether a patient with hemiplegia can walk independently in a ward. [Methods] The subjects were 15 physical therapists with experience of stroke patients’ rehabilitation. We interviewed them using semi-structured interviews related to the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Seven qualitative studies were included in this review, and their characteristics are summarised in detail in Table 3. Studies were conducted in Canada, 44,46 Norway, 47 Australia, 48 Japan, 49 the United States 50 and Saudi Arabia. 51 All six studies used interviews to collect data.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven qualitative studies were included in this review, and their characteristics are summarised in detail in Table 3. Studies were conducted in Canada, 44,46 Norway, 47 Australia, 48 Japan, 49 the United States 50 and Saudi Arabia. 51 All six studies used interviews to collect data.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…48 Most studies investigated clinical reasoning as part of a physiotherapy assessment of people with neurological conditions (n = 6). 44,49 The number of physiotherapists included in the studies ranged from 10 47 to 33. 48 Age and sex were described in only three studies, with participants being predominantly female 46 and age ranging from 20 to 50 years and over, 49 ranging from 20 to 50 years and over.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…35,36 In addition, regarding differences in disorders, many higher brain dysfunctions are known to interfere with ADL capability and walking. 37 Furthermore, a left-brain injury disorder has been known to produce lower ADL performance than a right brain injury. 38 Therefore, these studies indicate that ADL independence tends to be lower in patients with higher brain dysfunction and left cerebral hemorrhage.…”
Section: 79mentioning
confidence: 99%
“…Previous studies have found that outcome measures such as lower-limb muscular strength, [1][2][3] balance, [4][5][6][7][8] walking speed, [9][10][11][12][13][14] and cognitive function 15,16) are related to walking independence in elderly persons and in patients with stroke disease. However, outcome measures related to walking independence in patients with medical diseases have not been reported.…”
Section: Introductionmentioning
confidence: 99%